Enrichment of nutritional value of Phyllanthus emblica fruit juice using the probiotic bacterium, Lactobacillus paracasei HII01 mediated fermentation - Sartjin PEERAJAN (Food Science and Technology, 2016)
The fermented herbal juices are capable of curing and preventing diseases and reducing the aging progress. The present study was performed to investigate the fermentation of Phyllanthus emblica fruit by Lactobacillus paracasei HII01 with respect to carbon sources, polyphenols, and antioxidant properties. The physical changes, for instance, color, odor, taste, turbidity and gas formation, throughout the fermentation process was manually monitored. The fermented product was rich in polyphenolic content. The acid content and pH of the product were under the norms of Thai community product standards. Antioxidant properties of the fermented product were proved using ABTS, and FRAP assays. Chelation based study suggested that fermented P. emblica fruit juices are healthy enough to stabilize the oxidized form of the metal ion. The optimum fermentation period was 15 days. All the results supported that studied carbon sources did not interfere with the quality of the product. This report is the prelude study on the use of probiotic starter culture for the production of P. emblica fruit based lactic acid bacteria fermented beverages (LAFB) enriched with bioactive compounds. Further research on the impact of different carbon sources and upstream processes on the quality of LAFB is currently in progress.